2021
DOI: 10.1097/sle.0000000000000987
|View full text |Cite
|
Sign up to set email alerts
|

The Value of Preoperative Ultrasound in the Detection of Contralateral Occult Inguinal Hernia in the Treatment of Symptomatic Inguinal Hernia

Abstract: Background: The true incidence of contralateral occult inguinal hernia (OIH) is a debate. The repair of contralateral OIH in the treatment context of clinical symptomatic unilateral inguinal hernia (IH) is controversial. This study aimed to assess the effect and clinical benefit of preoperative ultrasound (US) in the diagnosis of contralateral OIH performed before surgery. Methods:The retrospective data of 155 consecutive male patients who underwent IH repair between January 2014 and January 2020 were analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…6 However, the incidence of contralateral occult inguinal hernia reported in the literature differs according to the diagnostic method used. Reported incidence values vary as 23.8% to 34.6% in studies using USG as a diagnostic method, 7,8 33% in studies using CT, 9 and 5% to 58% in studies using intraoperative surgical exploration. 6 In this study, the occult contralateral hernia was detected in 26 (25.5%) of 102 patients who underwent TAPP repair, in line with the literature data.…”
Section: Discussionmentioning
confidence: 99%
“…6 However, the incidence of contralateral occult inguinal hernia reported in the literature differs according to the diagnostic method used. Reported incidence values vary as 23.8% to 34.6% in studies using USG as a diagnostic method, 7,8 33% in studies using CT, 9 and 5% to 58% in studies using intraoperative surgical exploration. 6 In this study, the occult contralateral hernia was detected in 26 (25.5%) of 102 patients who underwent TAPP repair, in line with the literature data.…”
Section: Discussionmentioning
confidence: 99%
“…In performing the literature review, it was found one systematic review and meta-analysis [ 22 ], one systematic review [ 23 ], two narrative reviews [ 24 , 25 ], one clinical trial [ 26 ], eight observational studies [ [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] ], and one case series [ 35 ], that discussed the relationship between some risk factors, interventions and outcomes in the management of inguinal hernia.…”
Section: Risk Factors Interventions and Their Impact On Functional An...mentioning
confidence: 99%
“…Other cohort studies, such as those developed by Wright et al [ 28 ], Pierides et al [ 29 ], and Jarrard et al [ 30 ], which studied hernia growth, pre-operative pain, compressive neuropathy, and the presence of occult contralateral hernias, showed that these factors contribute to the development and persistence of chronic post-operative pain, which is associated with the presence of abundant fibrosis in the external oblique fascia at the level of the inguinal ring [ 28 ], higher risk of recurrence (OR 6.77, p = 0.005), complications (OR 5.16, p = 0.002) [ 29 ] and reoperation [ 30 ]. In the case of occult contralateral hernias, Ozgur et al [ 31 ] evaluated the usefulness of ultrasound in the pre-operative detection of this condition, finding that approximately 25% of cases present occult hernias, modifying the overall outcome of patients having to be reoperated days later [ 31 ]. Although not with the same performance and ease of access, dynamic magnetic resonance imaging can also aid in the visualization of structures and post-operative monitoring of mesh placement or fluid presence [ 35 ].…”
Section: Risk Factors Interventions and Their Impact On Functional An...mentioning
confidence: 99%
See 1 more Smart Citation